2015
DOI: 10.1021/jf505185u
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Laying Hens Stearidonic Acid-Enriched Soybean Oil, as Compared to Flaxseed Oil, More Efficiently Enriches Eggs with Very Long-Chain n-3 Polyunsaturated Fatty Acids

Abstract: The desaturation of α-linolenic acid (ALA) to stearidonic acid (SDA) is considered to be rate-limiting for the hepatic conversion of ALA to eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in humans, rodents, and chickens. Thus, we hypothesized that feeding laying hens SDA, as a component of the oil derived from the genetic modification of the soybean, would bypass this inefficient metabolic step and result in the enrichment of eggs with EPA and DHA at amounts comparable to that achieved by direct su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 39 publications
(61 reference statements)
10
63
0
1
Order By: Relevance
“…Using flax seed soil, the desaturation of α-linolenic acid (ALA) and docosahexaenoic acid (DHA) is considered to be slowest for the hepatic conversion of ALA to eicosapentaenoic acid (EPA) and DHA. Whereas soybean oil enriched with SDA reported to be readily incorporated into adipose tissue than into egg yolk, and as such more efficiently enriches eggs with very long-chain n-3 polyunsaturated fatty acids [70]. This suggests an alternate pathway for the hepatic secretion and transport of SDA in the laying hen.…”
Section: Manipulation Of Egg Nutrients-"designer Egg"mentioning
confidence: 94%
“…Using flax seed soil, the desaturation of α-linolenic acid (ALA) and docosahexaenoic acid (DHA) is considered to be slowest for the hepatic conversion of ALA to eicosapentaenoic acid (EPA) and DHA. Whereas soybean oil enriched with SDA reported to be readily incorporated into adipose tissue than into egg yolk, and as such more efficiently enriches eggs with very long-chain n-3 polyunsaturated fatty acids [70]. This suggests an alternate pathway for the hepatic secretion and transport of SDA in the laying hen.…”
Section: Manipulation Of Egg Nutrients-"designer Egg"mentioning
confidence: 94%
“…Individual fatty acids were separated and quantified by gas-liquid chromatography equipped with a fused-silica capillary column (SP2560; 100 m × 25 mm i.d. with 0.2-m film thickness; Supelco, Inc., Bellefonte, PA) and a flame ionization detector as described by Elkin et al (2015). Fatty acid concentration and methylation efficiencies were determined using dual external standards (13:0 free fatty acid and 17:1 methyl ester; Nu-Chek Prep, Inc., Elysian, MN).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Total RNA extraction, RNA concentration and quality assessment, and cDNA synthesis were determined as previously described (Elkin et al, 2015). Expression of long chain fatty acid desaturases (SCD1, FADS1, and FADS2), fatty acid elongases (ELOVL2, ELOVL5, and ELOVL6), a lipogenic enzyme (FASN), a cholesterol synthesis enzyme (HMGCR), fatty acid oxidation enzymes (CPT1a and ACOX1), lipogenic transcription factors (SREBP1 and MLX), and two housekeeping genes (BACT and B2M) was determined in quadruplicate by relative quantification SYBR Green Real-Time PCR (PerfeCTa ® SYBR ® Green Supermix with ROX TM , Quanta BioSciences, Gaithersburg, MD) using an 7900 Fast Real-Time PCR System (Applied Biosystems, Grand Island, NY).…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These results were applied to identify the effect of 176 each inducer and their interactions in the reaction. Figure 1 presents [21][22][23] . The major volatile compounds reported that the relative volatile composition changes according to the method used to perform the 249 analysis.…”
mentioning
confidence: 99%